OPTIMIZING THE WORKING CAPITAL OF SPARE PARTS IN AUTO SERVICE ENTERPRISES - Polvonov А.S; Аbdusattorov N.S.; Sulaymanov D.С.; Odilov J.A. (Western European Studies, 2024)
This article discusses the theoretical foundations of solving the problem of optimizing the volume of the working capital of spare parts and determining options for organizing the logistics support system (LSS) at car service enterprises
Keywords: technical service; car repair; car service services,